Оптимизация массогабаритных показателей регенераторов ГТУ - Кузнецов, В. В.; Соломонюк, Д. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
On the basis of optimization calculations efficiency use of the profiled heat-transfer surfaces for deriving gas turbine plants regenerator with minimum mass and overall indexes is shown. Recommendations at the choice of geometrical performances of the surface and boundary conditions for execution of calculation are reduced. Results of comparison mass and overall indexes the tube and the profiled surfaces are obtained